TASAWUF DALAM PANDANGAN ISLAM - Khairul Akbar, Muhammad; Nuh, Husaini; Lubis, Abdul Habib (Proceeding International Seminar of Islamic Studies, 2024)
Sufism is self-training to get used to being close to God with the aim of forming a person who always submits and obeys what He commands and prohibits. However, differences continue to occur in life with many different beliefs. This causes humans to distance themselves from God because the belief that was planted in them disappears, causing the ego of power to consume human life, causing them to return to teachings that deny God. The science of Sufism in Inayat's view opens the eyes of religion to see natural differences, not resistance or hostility, therefore it is stated in ten universal unities as the principles of Sufism that it believes in, namely: One God, even in various names. One true teacher must be present in various figures: Unity of our sacred (nature manuscripts), Unity of religion (path of truth), Unity of human brotherhood, Unity of moral principles (love), Unity in the object of praise (beauty), Unity of true truth (essential knowledge of self), One path of humanity (dissolution of the false ego towards the true ego).